Molecular Identification of Mudskipper Fish (Periophthalmus spp.) from Baros Beach, Bantul, Yogyakarta - Katon Waskito Aji; Tuty Arisuryanti (Journal of Tropical Biodiversity and Biotechnology, 2021)
Mudskipper fish is amphibious fish belonging to the family Gobiidae. Coastal communities widely consume mudskipper to meet their animal protein needs. Mudskipper is primarily cryptic species that are morphologically difficult to identify and distinguish from other mudskipper fish species. Consequently, it can be confused with the naming of mudskipper fish species and can affect the conservation efforts of the fish in their habitat. One of the molecular approaches that can be used to identify the fish species quickly and accurately is DNA barcoding using the COI mitochondrial gene. However, the research on the identification of mudskipper fish in Indonesia is still very limited. Therefore, this study aimed to identify 26 mudskipper fish from Baros Beach, Bantul, Yogyakarta, using COI mitochondrial gene as a molecular marker for DNA barcoding. The method used in this study was a PCR method with universal primers, FishF2 and FishR2. The data obtained were then analyzed using GeneStudio, DNASTAR, BLAST, Identification Engine, Mesquite, MEGAX, and BEAST. The analysis was conducted to obtain similarity, genetic distance and reconstruct a phylogenetic tree. The result revealed that all 26 samples of mudskippers collected from Baros Beach were identified in one genus, namely Periophthalmus, and consisted of 3 species, namely P. kalolo (16 samples), P. argentilineatus (9 samples), and P. novemradiatus (1 sample). Furthermore, this study also discovered a suspected cryptic species in P. argentilineatus with a genetic distance of 5.46-5.96% between clade E, F compared with clade G. Further morphological studies are needed to confirm the species status of these three clades before solidly proclaim that they are cryptic species.